2017
DOI: 10.1111/jgs.15127
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Prescribing in Hospitalized Older Adults: Patterns and Outcomes

Abstract: Background/Objectives Whereas opiate prescribing patterns have been well described in outpatient and emergency department settings, they have been less defined in hospitalized older adults. The objective was to describe patterns of opiate prescribing and associated outcomes in hospitalized older adults. Design Retrospective cohort study. Setting Tertiary care facility. Participants Hospitalized medical patients aged 65 and older (N = 9,245; mean age 80.3, 55.2% female, 72.3% white, 90.8% non‐Hispanic). Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…Other samples of hospitalized individuals have been smaller, investigated specific analgesics (e.g., opioids), or included more heterogeneous groups (e.g., mixed age groups or combined medical and surgical patients). [34][35][36][37] Although the prevalence identified in our study (20%) was lower than estimates of pain in community-dwelling adults (24-72%), [2][3][4] it is likely that this difference is because we focused on moderate to severe pain, whereas other studies Figure 3. Flow chart of opioid prescription before hospitalization, during hospitalization, and at discharge.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Other samples of hospitalized individuals have been smaller, investigated specific analgesics (e.g., opioids), or included more heterogeneous groups (e.g., mixed age groups or combined medical and surgical patients). [34][35][36][37] Although the prevalence identified in our study (20%) was lower than estimates of pain in community-dwelling adults (24-72%), [2][3][4] it is likely that this difference is because we focused on moderate to severe pain, whereas other studies Figure 3. Flow chart of opioid prescription before hospitalization, during hospitalization, and at discharge.…”
Section: Discussioncontrasting
confidence: 67%
“…Opioid therapy is one of the most frequently implicated medications in adverse drug reactions in the hospital . A recent study showed that hospitalized older adults who received opioids had longer hospital stays and were more likely to be readmitted . In our study, participants who had received outpatient opioids before hospitalization experienced longer hospital stays than those who did not.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…13 Studies of opioid-related adverse events in surgical inpatients suggest an association between older age, comorbidity severity, and opioid-related adverse events. [14][15][16] Nevertheless, multimorbidity remains an understudied and under-recognized reality in pain treatment guidelines. 2 Despite the high prevalence of pain and multimorbidity in older adults, little is known about patterns of analgesic treatment for these patients, particularly in the medical inpatient setting.…”
Section: Introductionmentioning
confidence: 99%